KONSEP MUTU MENURUT EDWARD DEMING,JOSEPH JURAN DAN PHILIPH B.CROSBY DALAM PERSPEKTIF PENDIDIKAN - Nurul Iflaha (P3M STAI MIFTAHUL ULUM LUMAJANG, 2023)
Quality can be interpreted as an absolute and relative concept. In the context of education, themeaning of quality is always based on the education system as a whole, starting from educationplanning, the education implementation process, education evaluation to education results inaccordance with the stated objectives. Basically, everyone agrees with efforts to improve the qualityof education, but then there is a perception or lack of common meaning about quality, and in theend it can be concluded that quality is a dynamic idea or quality is made into something that satisfiesand exceeds the desires and needs of customers. There are several quality concepts offered byexperts that can be applied in improving the quality of education, including Deming's quality conceptwhich combines these concepts starting from psychological insight to the obstacles in adopting aquality culture, Juran's quality concept with the trilogy theory, namely Quality planning, Qualitycontrol , Quality improvement, as well as Crosby's famous quality concept, namely the Zero Defectconcept. The type of research used is library research. Literature study is a research method carriedout by collecting and analyzing data or information originating from written sources such as books,journals, papers, articles and other documents.